Convective heat transfer - Kakac, Sadik (CRC, 1994)
The book offers knowledge about the physical mechanisms of convective heat transfer phenomena, exact or approximate solution methods and solutions under various conditions. Special attention has been given to the derivation of the basic equations of convective heat transfer and their solutions. It is assumed a basic knowledge of thermodynamics, heat transfer, fluid mechanics and differential equations. Convective heat transfer has great industrial importance. For practical use, important correlations are also listed whenever appropriate. Solved examples are given, and the problems of the end of each chapter are designed to clarify the physical and/or theoretically important points, as well as to supplement and extend the text. The Système International (S/I) is used as the system of unit in the solution of the problems